2012
DOI: 10.1002/jcp.22905
|View full text |Cite
|
Sign up to set email alerts
|

Role of insulin‐like growth factors (IGFs), their receptors and genetic regulation in the chondrogenesis and growth of the mandibular condylar cartilage

Abstract: Growth of the mandibular condylar cartilage (MCC) is reviewed as a function of genetic and epigenetic factors. The growth centers around the differential spatial concentration of the chondrocytes, influence of growth factors like TGF-β and heterogeneity in the number of IGF receptors, control the action of IGF. Besides these factors, growth of the mandibular condyle is influenced by differential response of chondrocytes as a function of their source/ageing, which in turn is regulated by TGF-β, BMPs and IGFs. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 121 publications
(136 reference statements)
2
21
0
1
Order By: Relevance
“…IGF-1 modulates MSC chondrogenesis by stimulating and increasing cell proliferation, regulates cell apoptosis, and induces in vitro expression of chondrocyte markers as proteoglycans and COL II [35,36]. IGF-1 has also been shown to improve chondrogenesis by increasing COL II and AGC expression when given in combination with TGF-β1, bone morphogenic protein-6 and TGF-β3 [12,37,38], but when administered alone is not sufficiently inductive in MSCs [39-41] or in ASCs, where exogenous protein was necessary in greater doses [42].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 modulates MSC chondrogenesis by stimulating and increasing cell proliferation, regulates cell apoptosis, and induces in vitro expression of chondrocyte markers as proteoglycans and COL II [35,36]. IGF-1 has also been shown to improve chondrogenesis by increasing COL II and AGC expression when given in combination with TGF-β1, bone morphogenic protein-6 and TGF-β3 [12,37,38], but when administered alone is not sufficiently inductive in MSCs [39-41] or in ASCs, where exogenous protein was necessary in greater doses [42].…”
Section: Discussionmentioning
confidence: 99%
“…S. In totality, these observations on the young rabbits reflected condylar growth, confirming earlier observations on mice and rats that IGF-1 and TGF-b complement the growth of MCC vascular endothelial growth factor. 6,14,15 The growth of the mandibular cartilage was evident by an increase in the length of the cartilage and an increase in the proliferative layer of the cartilage as shown in Figure 3 in the descending order AI . AS .…”
Section: Quantitative Assessment Of the Pg Content In The Condylar Camentioning
confidence: 99%
“…However, the successful generation of stable hyaline cartilage tissue using MSCs requires the efficient delivery of the factors stimulating chondrogenesis [1,15]. Many studies have reported that certain growth factors, such as transforming growth factor (TGF)-βs [16,17], bone morphogenetic proteins (BMPs) [18,19], fibroblast growth factors (FGFs) [20], and insulin-like growth factor (IGF)-1 [21,22], are capable of directing MSCs to chondrocyte phenotypes. However, these growth factors have not been extensively used due to their limited abilities to synthesize specific cartilage matrix components.…”
Section: Introductionmentioning
confidence: 99%